Status of serum zinc level in patient with pulmonary tuberculosis - Towhid, Ferdous; Lisa, Nazma Akther; Banik, Shyamal Chandra; Shah, Kartick Chanda; Islam, Tanzida (Journal of Dhaka National Medical College & Hospital, 2020)
Background: Tuberculosis is an infectious disease caused by the bacillus Mycobacterium tuberculosis. Bangladesh ranks 6th among 22 highest burden TB countries in the world. Micronutrient deficiency is common in pulmonary tuberculosis but still poorly documented. Zinc is essential for immune function, deficiency of zinc lead to impaired immunity and thereby increases susceptibility to infections such as tuberculosis. Several studies in abroad have demonstrated that the serum zinc level is decreased during active pulmonary tuberculosis. The aim of this study is to determine serum zinc levels in pulmonary tuberculosis patients. Objective: To assess the serum zine level in pulmonary tuberculosis patient and healthy individual. Methods: A descriptive, cross sectional study was conducted from January 2016 to December 2016 among 50 pulmonary tuberculosis patients attending at Respiratory Medicine Department of the Dhaka Medical College Hospital and 50 healthy individuals, after obtaining requisite consent from the patients. Data were collected through the interviewing of the patients. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to assess the serum zinc level in pulmonary tuberculosis patients and healthy individuals. The study was approved by the institutional ethical committee. Results: In a pool of 50 tuberculosis patients and 50 healthy individuals, serum zinc (μmol/l) (mean + SD) level was significantly lower (p <0.001) in pulmonary tuberculosis without treatment (8.9 + 2.1) than normal individuals (15.6 + 4.8). Conclusion: Serum zinc level was significantly lower (p <0.001) in pulmonary tuberculosis patients without treatment. Zinc rich food and zinc supplementation may be helpful to improve the immune status of TB patients. J. Dhaka National Med. Coll. Hos. 2020; 26 (01): 08-10